Unmanned aerial vehicle, and GIS tools, to monitor the reproduction of the flamingo Phoenicopterus chilensis (Aves: Phoenicopteridae) - Luque-Fernández, César R.; Caballero, Kenny; Pauca, Gregory Anthony; Villegas, Luis; Alcelay, Ibai; Machaca, John (Revista de Biología Tropical, 2021)
Introduction: High Andean flamingos also known as parihuanas, are species of recurrent presence in the high Andean areas which find this area as an important resting, feeding and in some cases breeding area The species recorded here correspond to Phoenicoparrus jamesi, Phoenicoparrus andinus and Phoenicopterus chilensis, the latter being the most abundant and common. During the censuses performed during 2018 and 2019, in the high Andean lake of Salinas, Ramsar site, located within the Reserva Nacional Salinas y Aguada Blanca in Southern Peru, atypical behaviors of these birds were recorded in a sector of the lake, observing reproductive courtship and the settlement of colonies of P. chilensis. Objective: The study aimed to confirm and evaluate reproductive events of P. chilenesis (Chilean flamingo) through the use of an unmanned aerial vehicle (UAV) and image processing tools using geographic information systems. Methodology: Monitoring was conducted during 2018 and 2019 to breeding colonies of P. chilensis, we used a UAV Phantom 4 testing different flight altitudes to avoid disturbing the birds and performed records of aerial photographs and GIS post-processing with the creation of panchromatic images for the identification and counting of individuals and eggs automated, and manual verification. Results: During 2018 were identified nests and presence of six eggs, this occurred between March and June where the event was interrupted not observing chicks or juveniles during this period, for 2019 the breeding was more successful, where a higher number of eggs were counted (40-66) and with the formation of three reproductive colonies with 4 185 adult individuals, also verified the presence of chicks and juveniles that reached a maximum of 1 491 individuals. Conclusions: We confirmed two continuous reproductive events of P. chilensis in the Salinas lake, where during 2019 was the most successful incorporating several new individuals to the initial population, likewise the methodology applied in the image processing allowed differentiating between adult individuals and eggs but did not allow differentiating juveniles, however, the images directly acquired by the UAV allow distinguishing the types of individuals to perform a manual count.